2020
DOI: 10.1038/s41388-020-1244-1
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin prevents a miR-dependent negative regulation of tissue factor mRNA during epithelial–mesenchymal transitions and facilitates early metastasis

Abstract: Epithelial-mesenchymal transitions (EMTs) are high-profile in the field of circulating tumor cells (CTCs). EMT-shifted CTCs are considered to encompass pre-metastatic subpopulations though underlying molecular mechanisms remain elusive. Our previous work identified tissue factor (TF) as an EMT-induced gene providing tumor cells with coagulant properties and supporting metastatic colonization by CTCs. We here report that vimentin, the type III intermediate filament considered a canonical EMT marker, contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Interestingly, a relationship between TF expression and CSC phenotypes has also been reported [235,236]. The EMT core transcription factors ZEB1 and Snail were delineated to regulate TF expression [234], and recently, vimentin was reported to stabilize TF mRNA [237]. Interestingly, TGF-β, liberated from activated platelets, has been described to trigger EMTs [142], suggesting a regulatory loop between EMT and platelet activation.…”
Section: Activation Of Coagulationmentioning
confidence: 95%
“…Interestingly, a relationship between TF expression and CSC phenotypes has also been reported [235,236]. The EMT core transcription factors ZEB1 and Snail were delineated to regulate TF expression [234], and recently, vimentin was reported to stabilize TF mRNA [237]. Interestingly, TGF-β, liberated from activated platelets, has been described to trigger EMTs [142], suggesting a regulatory loop between EMT and platelet activation.…”
Section: Activation Of Coagulationmentioning
confidence: 95%
“…Tissue factor (TF) is a 47 kDa membrane-associated glycoprotein, which has recently been identified as a link between the hemostatic system and cancer progression [ 135 ]. It is observed that vimentin stabilises TF mRNA, thus promoting coagulant activity and early metastasis [ 136 ].…”
Section: Vimentin Regulating Other Genes During Emtmentioning
confidence: 99%
“…Vimentin is a structural protein found in cells of mesenchymal origin, though it has also been described in activated monocytes, and to a much lesser extent in lymphocytes 42‐45 . It has been associated with the procoagulant effects of metastatic tumor cells through a TF‐dependent mechanism 46 . We therefore examined vimentin expression in and around transplanted islets.…”
Section: Resultsmentioning
confidence: 99%